IMPACT OF FIRM SPECIFIC FACTORS ON PROFITABILITY OF INDUSTRIAL GRINDING COMPANIES - Milošević Avdalović, Snežana (Economics of Agriculture, 2018)
In this paper, panel ordinary least squares model of industrial grinding companies listed on Belgrade Stock Exchange was used for examining the determinants of proftability. For this purpose, 62 observations of companies over the period of 2008 – 2014 were included. Return on equity considered as a measure for proftability is a dependent variable whereas size, leverage, years of frm existence, number of stock and book value per share are considered as independent variables. According to the fndings, leverage, number of stock and book value per share are statistically significant of inverse relationship with proftability for selected listed industrial grinding companies in Serbia. Size (+) and age (-) indicate insignifcant impacts on proftability. The results revealed that all independent variables explain 84.4% of the variance on return on equity. The results of Granger causality test indicated causality between proftability and leverage, proftability and number of stocks are bidirectional.